The Implikatur Pidato Politik Anies Baswedan Terima Deklarasi Capres Pilpres 2024 Dari Nasdem - Tamaratul Qalbi Maisaroh (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
This research is motivated by the implicature in the video of Anies Baswedan's first political speech receiving the presidential candidate's declaration for the 2024 presidential election from Nasdem on the YouTube platform. The aim of this research is to describe the types and meaning of implicatures in Anies Baswedan's speech in the video of his first political speech accepting the presidential candidate's declaration for the 2024 presidential election. This research is included in qualitative research using a descriptive approach. The data in this research is oral data in the form of speech which has been classified based on the type and meaning of implicatures contained in the video of Anies Baswedan's first political speech receiving the presidential candidate declaration for the 2024 presidential election from Nasdem. The research results show that there are types and meanings of implicatures in Anies' speech in the video of the declaration of his first political speech. Anies Baswedan received the presidential candidate declaration for the 2024 presidential election from Nasdem. The types of implicatures found in this research are conventional implicatures and conversational or non-conventional implicatures. Meanwhile, the meaning of implicatures found is in the form of referential and non-referential meanings.